Maximizing taper in aquatic - Mujika, I. (FINA World Sports Medicine Congress, 18, 2016)
Dr. Iñigo Mujika, Sports Training and Physiologist talks about "Maximizing Taper in Aquatics" at the FINA World Sports Medicine Congress 2016 (28:42 min).